The expansion of alternative food to conventional food in Espírito Santo - de Gouveia, Kedma de Andrade Nogueira (Geografares, 2018)
This study aims to analyze and map the main actors of the unconventional food production’s expansion in Espírito Santo (ES) from the end of 1960 until the end of 1990, when that food was called "alternative" to conventional. In order to develop the study, the research was conducted at historical organizations, websites, through ethnographic experience with farmers, street market and at the farm’s production. The farmers and the food’s path in the state were identified and represented trough graphs. It was also analyzed the historical institutions that highlights in the agroecological development at the state. It has been given emphasis to Associação de Programa em Tecnologias Alternativas (APTA), Associação de Produtores Santamarienses em defesa da Vida (APSAD-VIDA) and to Associação Chão Vivo.Key words: food, allternative agriculture, street market, networks.